Lubrication with water-based clay suspensions - Briscoe,BB; Cann,PM; Delfino,A; Maitland,G (Proceedings of the World Tribology Congress III 2005, 2005)
The lubricating behaviour of a water-based rock drilling fluid (bentonite clay suspension) has been studied in a simple tribometer. Friction measurements were carried out with a model contact formed between a rotating shaft and a loaded planar counterface. The experiments were designed to investigate the tribology of the contact between the drillstring and the metal wall of an oilwell. Friction measurements were made for a range of loads and contact velocities and clay concentrations. The results are presented in the form of classical Stribeck-Hersey curves in order to identify the lubrication regime and to illustrate the combined effects of load and speed on the friction coefficient. Optical interferometry experiments were also carried out, using a ball-on-disc apparatus, in order to visualise the flow of the suspension through the contact. In a separate series of tests the interfacial shear stress of the mud formulations was measured for different contact metallurgies and operating conditions. Two basic lubrication regimes are identified: at high loads a regime characterised by the deposition of layers of solid clay onto the contacting surfaces and at low loads, a regime in which the main lubricating action is provided by the base fluid. In the transition between the two regimes, an intermediate region is characterised by changes in the fluid composition and rheology within the contact. The general trend of the Stribeck curve is obtained and a peculiar scattering of the data is evident in the region between the boundary lubrication regime and the mixed lubrication regime. The intrinsic nature and the complex rheology of the fluid appear to be the parameters that may control this effect and in part define the lubrication regime. Copyright © 2005 by ASME.